2010
DOI: 10.1016/j.lfs.2010.07.008
|View full text |Cite
|
Sign up to set email alerts
|

l-NAME-treatment alters ectonucleotidase activities in kidney membranes of rats

Abstract: The general increase in ATP hydrolysis and in ecto-5'-nucleotidase activity suggests a rise in renal adenosine levels and in renal autoregulatory responses in order to protect the kidney against the threat presented by hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 41 publications
2
20
0
Order By: Relevance
“…This result is in agreement with previously described studied by Balbinott et al (2005). Also, many authors have reported the ability of the arginine analog, L-NAME, to induce systemic arterial hypertension (Furstenau et al, 2008(Furstenau et al, , 2010Cardoso et al, 2012Cardoso et al, , 2014, which probably occurs due to the capacity of L-NAME to inhibit the production of nitric oxide, a well known vasodilator molecule, by blocking nitric oxide synthase (NOS) activity (Moncada et al, 1991). However, dietary supplementation with both rhizomes and treatment with a positive control drug (atenolol) caused a significant reduction of SBP in the hypertensive rats (Fig.…”
Section: Mol Ache/h/mg Proteinsupporting
confidence: 90%
See 2 more Smart Citations
“…This result is in agreement with previously described studied by Balbinott et al (2005). Also, many authors have reported the ability of the arginine analog, L-NAME, to induce systemic arterial hypertension (Furstenau et al, 2008(Furstenau et al, , 2010Cardoso et al, 2012Cardoso et al, , 2014, which probably occurs due to the capacity of L-NAME to inhibit the production of nitric oxide, a well known vasodilator molecule, by blocking nitric oxide synthase (NOS) activity (Moncada et al, 1991). However, dietary supplementation with both rhizomes and treatment with a positive control drug (atenolol) caused a significant reduction of SBP in the hypertensive rats (Fig.…”
Section: Mol Ache/h/mg Proteinsupporting
confidence: 90%
“…Alterations in the activities of this enzyme complex have been verified in various studies in hypertensive patients (Schetinger et al, 2007;Lunkes et al, 2009;Bagattini et al, 2011;Cardoso et al, 2012). Regarding L-NAME-induced hypertension in rats, it has recently been demonstrated that ectonucleotidase activities are altered in these enzyme activities in different tissues (Furstenau et al, 2008(Furstenau et al, , 2010Cardoso et al, 2012). Nevertheless, our study report for the first time, to the best of our knowledge, alterations of ectonucleotidase activities in cerebral cortex synaptosomes in L-NAME-induced hypertensive rats.…”
Section: Mol Ache/h/mg Proteinsupporting
confidence: 62%
See 1 more Smart Citation
“…A 2A receptor knockout mice had increased proliferation of endothelial cells and increased smooth muscle hypertrophy and collagen deposition in the pulmonary arteries and increased wall area thickness and smooth muscle actin immunoreactivity in the pulmonary resistance vessels, suggesting that adenosine, acting at A 2A receptors, is an important regulatory mechanism to protect against development of pulmonary arterial hypertension . Increased ATP hydrolysis by ectonucleotidases resulting in an accumulation of adenosine in the kidney of hypertensive animals has been reported (Fürstenau et al, 2010).…”
Section: A Hypertensionmentioning
confidence: 99%
“…ATP-induced hypotension is associated with alteration of sympathetic nerve activity mediated through vagal afferent pathways [366]. It has been reported that there is an increase in ATP hydrolysis resulting from an increase in ecto-5′-nucleotidase activity and accumulation of adenosine in the kidney of hypertensive animals [96]. A high salt diet given to Ang II hypertensive rats significantly impairs autoregulation of rat juxtamedullary afferent arterioles, which is associated with a decline in afferent arteriolar reactivity to ATP mediated by P2X1 receptors [154].…”
Section: Hypertensionmentioning
confidence: 99%